The Need for Introduction of Sharia Microfinance Program in the Gambia - Saikou Gassama; Hamidah; Erina Sudaryati (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
The Gambia is a 95 percent Muslim country that is located in the western part of Africa. The population of the country is around 2.5 m. The Gambia is largely dependent on Agriculture, tax, tourism, and foreign aid and is ranked 178, in the Human Development Index 2019, the Gambia is classified as a country with medium human development. The paper used the literature review method. Currently, there is various microfinance program that has been existing for years, but none of them are having Islamic microfinance loan products until recently when two are lunched, as a result, some did not take their loans and even those who take it is hard to change their lives because it is purely for profit-making and also the higher interest rate for some of them. Islamic Microfinance would be the best development instrument for the population of Gambia. The microfinance institutions in The Gambia are very well expanded, they are the main source of credit to the Gambian population both rural and urban. Therefore it will be very important if microfinance institutions in the Gambia can introduce sharia microfinance. The objective of this paper is to suggest ways to introduce sharia microfinance in The Gambia and the benefits of sharia microfinance. The results of this study find out that Islamic microfinance is a viable loan product that can work in the Gambia, there are various kinds of Islamic microfinance products that can work for the poor in the Gambia, such as farmers, gardeners, and market vendors or SMEs. And Islamic microfinance could be the best way of eradicating poverty in the Gambia, since it is not based on the predetermined interest rate and have various suitable loan schemes, if well implemented can change lives.